Degree of oxidation of sonicated soybean oil using various sonication process parameters. (29th April 2022) - Lee, Juhee; Legako, Jerrad F.; Martini, Silvana
Summary: This research aimed to examine the effect of high‐intensity ultrasound (HIU) on the oxidation of soybean oil (SBO). Samples (5, 100, and 250 g) were sonicated at 25 °C using various sonication conditions: power level (settings 1, 5, and 9), tip size (12.7, 3.2, and 2 mm), and duration (5, 10, and 60 s). After sonication, the degree of oxidation of samples (sonicated and non‐sonicated SBO) were analysed using peroxide value (PV), oil stability index (OSI), and volatile compounds. Sonication was applied to obtain a range of absolute power (0–123.5 W), power density (0–14.2 W cm −3 ), and power intensity (0–1, 120 W cm −2 ) values. The highest power density and power intensity were obtained with the highest HIU setting with the 3.2 mm tip. The highest power was obtained when HIU was applied using a 12.7 mm tip and setting 9 in 250 g of sample. No significant difference ( P  > 0.05) was observed in PV (0.20 ± 0.01 mEq kg −1 ) nor OSI (10.05 ± 0.04 h), among the various sonication conditions tested. In addition, no differences were observed in the volatile compounds obtained. These results show that HIU can be used under mild sonication conditions such as the ones needed to change the physical properties of lipids without causing oxidative deterioration. Abstract : This graphical abstract shows that the application of high‐intesity ultrasound to soybean oil using various sonication conditions relevant to the sonocrystallization of lipids does not affect its oxidation.